RAKTA DHATU: AN AYURVEDIC REVIEW - Dr Jyoti Yadav, Dr Deepak Sharma (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2018)
Dhatu offers Ashraya, that may Dharana &Poshanai.e. supports & nourishes the body by its prakrita karmas. There are seven dhatu in our ayurvedic classic like as Rasa, Rakta, Mamsa, Meda, Asthi, Majja, Sukra. Raktadhatu is second dhatu. Teja &jalamahabhuta is predominant in raktadhatu.The moola sthanas of Raktavahasrotas unit of measurement yakrut (liver) and pleeha (spleen). Rudhirm, Astrak, Lohitam, Sonitam unit of measurement the synonyms of the raktadhatu. Jivan is that the most perform of raka dhatu. keep with Acharya charak, Raktadhatu has eight anjalipramana. Sira and kandara unit of measurement the upadhatu of rakta. Raktadhatu zygomatic bone is piita once raktadhatupramana created in utttam,avar, madhymaavastha individuals spoken as raktasara purusha. Any moderately derivation in raktadhatu winds up in pathological process. KEYWORDS :Rakta Dhatu, Raktavahasrotas, VishudhaRakta Dhatu.